IMPLEMENTATION OF STATE SOCIAL POLICY OF UKRAINE IN TERMS OF REFORMING PUBLIC AUTHORITIES - Korotych O.B. (Pressing Problems of Public Administration, 2016)
Implementation of state social policy in Ukraine is facing a number of problems, some of which arenew, additional challenges associated exclusively with the present conditions that aggravate thesocial, political, and financial instability. In this regard, a systemic reform of public authority in Ukrainedeserves special attention.